Stronger sex but earlier death: A multi-level socioeconomic analysis of gender differences in mortality in Austria - Martin Gächter; Peter Schwazer; Engelbert Theurl (University of Innsbruck, Department of Public Finance, 2010)
Gender inequalities in mortality/life expectancy have been a major area of research in the social sciences since the 1970s. However, the questions posed and the research strategies used are still in a state of flux. In the present paper we shed some light on two related questions: (i) Which socioeconomic variables determine the gender gap in mortality? (ii) Are male and female mortality rates determined by different socioeconomic factors and in different shapes? We use aggregated data from Austria both at the community and district level covering the time period 1969 - 2004. Our two-level empirical design combined with a panel structure at the districts level reveals additional evidence on these questions compared to previous studies at the regional level. By using weighted regression analysis (panel fixed effects, pooled and cross section) we find that the gender gap is negatively associated with higher average net income, a higher educational level, a higher share of immigrants and better familial integration. In general, males are more sensitive with respect to social and economic conditions compared to females, leading to a narrowing gap in mortality when living conditions improve. These results are also confirmed by our Blinder-Oaxaca Decomposition.
Keywords: I12; I18; J16; 330; mortality; gender mortality gap; life expectancy; Austria; Sterblichkeit; Geschlecht; Österreich